Well-versed exploring modern Japanese haiku - Ozawa, Minoru 1956- (Japan library (Shuppan Bunka Sangyo? Shinko? Zaidan))
"This volume of seasonally-arranged poems is a guide to the appreciation and enjoyment of the great variety of modern Japanese haiku. From turn-of-the-century masters to poets of today, 300 of Japan's best modern haiku are introduced by OZAWA Minrou, a leading contemporary haiku poet and critic. Each of the poems, many of them scarcely known, is sensitively discussed together with the background of the poem and the relations between the poets. This volume includes poems from the end of the nineteenth century through the beginning of the twenty-first century by the most important writers of modern haiku. they include the leading lights from grounds surrounding MASAOKA Shiki and his disciple TAKAHAMA Kyoshi as well as poets who experimented with new styles such as seasonless haiku, free form haiku, and multi-line haiku. Alongside these are works by well-known novelists and other cultural figures who were not professional haiku poets but for whom haiku was an important part of their lives, such as KUBOTA Mantaro?, AKUTAGAWA Ryu?nosuke, and NATSUME So?seki. The book also features beautiful seasonal photographs at the beginning of each chapter, and an additional 20 haiku by the author." --